SHOROF AS AN ESSENTIAL FOUNDATION IN UNDERSTANDING CLASSICAL ISLAMIC TEXTS TO STRENGTHEN STUDENTS' COMPETENCE IN ISLAMIC KNOWLEDGE - Haryanto, Toat; Nafiuddin, Nafiuddin; Huda, Miftahul (UIN Maulana Malik Ibrahim Malang, 2025)
Islamic education in Indonesia, especially in pesantren, heavily relies on a deep understanding of the classical texts (kitab kuning) written in Arabic. Shorof, as a science studying the changes in word forms in Arabic, plays a fundamental role in helping students comprehend these texts. This research aims to explore the role of Shorof as a crucial foundation in understanding the kitab kuning and how it strengthens students' competencies in Islamic studies. The methodology used in this study is a qualitative approach with library research analysis. The study found that a good command of Shorof allows students to understand religious texts more deeply and accurately. However, there are still weaknesses in Shorof teaching methods, which are often limited to memorizing rules without application to the context of the kitab kuning. This research recommends a more practical teaching approach and the use of technology to facilitate the understanding of Shorof. The main contribution of this study is to provide insights into the importance of Shorof in Islamic education and offer solutions to optimize the teaching of Shorof in a more contextual and relevant way to the current needs of students.